The Role of Literacy in Class 1 Teaching and Learning Activities of Elementary Schools in Jepara - Sufa, Laila Nurul; Supriyanto, Teguh; Prihatin, Titi (Educational Management, 2021)
This study aims to determine basic literacy in teaching and learning activities for grade I elementary schools in Jepara. The research used a qualitative approach with descriptive research methods using data collection techniques such as observation, interview and documentation. The research subjects were school principals and grade I teachers of SDN 1 Kalipucangwetan. The results of the study explain that basic literacy in teaching and learning activities in class I has a role as (1) activities that help achieve learning objectives. Literacy activities can be placed in the core activities of the lesson plan. The teacher designs learning activities as well as literacy activities (2) Media literacy can be a learning medium. The media used by the teacher is in the form of media that can be good teaching aids for literacy activities that are combined with teaching and learning activities. (3) The materials used for literacy are the same as class I subject matter, especially in alphabet, phoneme and vocabulary materials. Teaching materials that become literacy materials are adjusted to the pleasant first class characteristics